Hierarchical architectures of Co3O4 ultrafine nanowires grown on Co3O4 nanowires with fascinating electrochemical performance. (9th November 2015) - An, Lei; Yu, Li; Cao, Yunjiu; Li, Wenyao; Xu, Kaibing; Ji, Tao; Zou, Rujia; Hu, Junqing
Abstract : The hierarchical Co3 O4 nanowires@Co3 O4 ultrafine nanowires as electrodes delivered high specific capacitance, superior rate performance and long lifespan. Abstract : A facile method to synthesize hierarchical architectures of Co3 O4 nanowires@Co3 O4 ultrafine nanowires grown on Ni foam was developed here. The unique architectures consisting of numerous ultrafine Co3 O4 nanowires (shell) well grown on the surface of a Co3 O4 nanowire (core) delivered remarkable electrochemical performance with ultrahigh specific capacitance (1640 F g −1 at a current density of 2 mA cm −2 ), superior rate capability (66% retention of the initial capacitance from 2 mA cm −2 to 50 mA cm −2 ) and outstanding cycling stability (∼99.03% retention of the initial capacitance after 10 000 cycles). Such fascinating capacitive behaviors can make these hierarchical architectures of Co3 O4 nanowires@Co3 O4 ultrafine nanowires promising electrode materials in electrochemical applications.